RELEVANSI NILAI ETIKA BISNIS DALAM RUANG LINGKUP AKUNTANSI SYARIAH - Nurul Mawaddah; Indra Wijaya (Syiah Kuala University, 2016)
Today, the development of ethics and Syariah business behaviour need to note. It is undeniable that globalization has brought great influence on how the behavior of businesses today, therefore influence to the deterioration of ethical standards. Then the Priest of Islam reconstruct how ethics and behaviors that are considered authentic coming from Islam. Ethics in business conduct in business syariah Islam teaches that every human being should uphold the values of honesty, trust, professional and work together. Based on the concept of justice, togetherness in the business and there is no element of riba. An accountant must have business ethics in the presentation of financial statements because it must be able to present information that can encourage economic actors to act fairly, honestly and properly, and able to provide other information such as basic information for calculating zakat. Another goal may be adopted from the goal applied in western countries for that purpose do not conflict with Islamic law.